B.Ed. Students’ Ability of Identifying Focal Points and Command Words in a Question to Develop Appropriate Answer — A Study - Rathod, Nikita; Ramachary, A. (JOURNAL OF INDIAN EDUCATION, 2013)
Questions set for B.Ed students’ evaluation process contain few focal points as well as some command words to be addressed in offering appropriate answers to the questions asked in the examinations. Noting poor performance of prospective teachers in their own ability of identifying focal points and command words in the question papers, an effort was made to test the same. In the present study, with a quality concern in the evaluation dimension, the diagnostic observations were done from the performance of 69 B.Ed. students in their internal tests. An attempt was made to develop material for due orientation to improve their ability to understand the true meaning and role of focal points and ability to address the command words in the questions asked in the examinations. Besides, this study reveals the improvement in the final exam performance, after the remedial orientation, confirming the positive influence of the treatment for both the vernacular and English medium students at B.Ed level.